1970
DOI: 10.1103/physrevlett.24.738
|View full text |Cite
|
Sign up to set email alerts
|

ac-Josephson-Effect Determination ofehwith Sub—Part-Per-Million Accuracy

Abstract: PHYSICAL REVIEW LETTERS 30 MARCH 1970 dR LM /dr* = [V LM (r)-u 2 ]K LM .Fortunately, the problem has a solution (many, in fact, since it turns out that one of the functions/, g, h, k, or n may be chosen arbitrarily).If we let n(r) = l-2m/r where m is the mass of the Schwarzschild field we find that f(r) = [x(X + l)r 2 + 3\mr + 6m 2 ]/r 2 (\r + 3m), g(r) = 1,and that r* = r + 2mln(r/2m-l),so thatwhere T/ , x /l-2m\2x 2 (X + l)r 3 + 6X 2 mr 2 4.18Xm 2 r + 18m 3 ,-.Note that the system (4) written as a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1971
1971
1976
1976

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 10 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…In a recent paper on the experimental test of the theory of muonic atoms, Dixit et al 1 have reported measurements of muonic x-ray energies in a number of elements in the energy range 150-440 keV. They picked for measurement only the higher transitions in atoms with spherical nuclei and made special efforts to measure these transitions with an absolute precision of 15-21 eV.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper on the experimental test of the theory of muonic atoms, Dixit et al 1 have reported measurements of muonic x-ray energies in a number of elements in the energy range 150-440 keV. They picked for measurement only the higher transitions in atoms with spherical nuclei and made special efforts to measure these transitions with an absolute precision of 15-21 eV.…”
mentioning
confidence: 99%
“…The prinicpal correction to the Dirac energy in this energy range turns out to be that due to e ~-e + vacuum polarization. These corrections were calculated by Fricke 2 ; and, using these calculated numbers, Dixit et al 1 arrived at their theoretical values for the transition energies. Corrections due to nuclear polarization, the screening effect due to electrons, the Lamb shift and relativistic corrections to the reduced mass, etc.…”
mentioning
confidence: 99%
“…On the basis of the 1967 comparison, our values and those of the University of Pennsylvania [6,18,19] are unlikely to differ by more than about 0.5 ppm.…”
Section: Resultsmentioning
confidence: 57%
“…4 It has also been observed 1 ' 2 that the present accurate experimental values for v m and MJU/MB permit an independent determination of the fine-structure constant a with an accuracy comparable with that of the Josephson effect. 5 For these reasons, it is desirable to have a theoretical expression for v m which accurately accounts for the muon recoil.…”
mentioning
confidence: 99%